Tinjauan Yuridis Influencer Dibawah Umur yang Tidak Membayar Pajak Berdasarkan Undang-Undang Nomor 36 Tahun 2008 Tentang Pajak Penghasilan - Zahra Humaira Febriyanti; Abdul Rohman (Bandung Conference Series: Law Studies, 2024)
The main source of the state comes from taxes, so the government imposes tax obligations as one of the state obligations for the benefit of the state. Tax is a payable and forced payment payable under tax regulations. Income tax is a tax imposed on taxpayers on income earned in a tax year and has the economic ability received from wherever it comes from to increase wealth. The development in social media is useful for earning income, so endorsement work has emerged, namely to promote products online carried out by underage influencers. So underage influencers earn income from endorsement services, according to tax regulations are obliged to pay tax to the state on the income earned. Based on the description above, the author formulates several problems as follows: First, what is the responsibility of underage influencers to the obligation to pay taxes? Second, what are the legal consequences for underage Influencers with taxable income. The scientific effort of the research method uses normative juridical research sourced primarily from statutory, secondary, tertiary and library materials as well as research specifications with a descriptive approach of analysts to obtain answers to the problems studied. Based on the results of the study, the responsibility of underage influencers for the obligation to pay taxes under the UU PPh is the income of immature children, regardless of the source of income and whatever their work will be combined with their parents' taxes in the same tax year. Legal consequences for underage Influencers with taxable income not paying taxes tax legislation will be subject to administrative sanctions increased by 50%. Under civil law, the sanction will be transferred to the parent because it is under his supervision. For dispute resolution to taxpayers due to a tax assessment letter that is subject to administrative sanctions in the form of an increase but the taxpayer does not agree, it can resolve tax dispute resolution by submitting an objection to the Directorate General of Taxes.